Neoplasm-induced bleeding in inherited, heterozygous FXIII-A deficiency - Ivaškevičius, V.; Goldmann, G.; Biswas, A.; Westhofen, P.; Thomas, A.; Marquardt, N.; Horneff, S.; Klein, C.; Rühl, H.; Pötzsch, B.; Oldenburg, J. (Hämostaseologie, 2015)
Inherited mild factor XIII deficiency belongs to one of the most underdiagnosed bleeding disorders so far. This is, because most patients do not develop bleeding complications in daily life.A man (age: 64 years) without a history of bleeding presented with painful swelling of neck, weight loss, anemia and episodic bleeding from the right tonsil necessitating tonsillectomy. Histologic and immunohistochemical evaluation revealed cytokeratinpositive epitheloid angiosarcoma. Blood coagulation status showed significantly elevated D-dimer and decreased FXIII levels (FXIII-activity 35%, FXIIIA-Ag 16–26%). Plasma mixing studies excluded neutralizing antibodies against FXIII.A novel heterozygous F13A1 gene nonsense mutation (p.Glu103Ter, c.307G>T) was found confirming heterozygous FXIII-A deficiency. The same mutation was detected in two further asymptomatic relatives. For further clinical management the patient was transfused with FXIII-concentrate and showed an adequate increase of FXIII ruling out FXIII deficiency to be induced by increased turnover. Despite this haemostatic management and antifibrinolytic treatment the patient had to undergo several revisions due to delayed, Hb relevant bleeding after cervical lymph nodes extirpation and resection of tonsil. Two chemotherapy cycles with paclitaxel and palliative radiotherapy of the neck area were performed, but the patient died unfortunately two months after diagnosis.It is a unique case showing the combination of a highly aggressive angiosarcoma and presence of inherited FXIII deficiency. It is also a rare example demonstrating the benefit of FXIII genotyping besides the expected acquired FXIII deficiency possibly due to neoplasm induced increased consumption by elevated crosslinking of fibrin fibers.
Keywords: FXIII; acquired FXIII deficiency; inherited FXIII deficiency; F13A1; F13B